METAMORFOSIS MEDIA KOMUNIKASI PEMASARAN PRODUK HASIL USAHA MIKRO KECIL DAN MENENGAH - Christantyawati, Nevrettia; Sufa, Siska Armawati; Susilo, Daniel; Putranto, Teguh Dwi (UNIVERSITAS PGRI MADIUN, 2018)
Abstract.Determination technology has changed the face of the world in all sectors. Especially industrial sectors and trade that the impact is very large. A technological revolution that touches all economic and social environments strongly forces all business people to switch from conventional to digital technology. Despite a necessity, this internet technology revolution is not necessarily able to push over control. It is still to be considered how the condition of economic community readiness of Small and Medium Enterprises in implementing this digital technology. This article is a series of research results and services to the public on how to get around the marketing communications communication from conventional analog-communication technology and manual industry technology. Some of the focus that will be discussed include the trick of increasing the competitiveness of UMKM Production Center of Aneka Keripik through the implementation of marketing communication technology transfer through modern technology transfer. The direct target is to increase the productivity of the business resulting from the potential cultivation of the plantation sector. The research object base is focused on communication synergy between institutions related to marketing of MSMEs in Tuwiri village, Merakurak sub-district, Tuban regency of East Java, and implementation of marketing communication system conducted by UMKM business actors including assessment of marketing communication mode and product distribution pattern through online and delivery system order.Keywords: Technology transfer, Marketing Communications, SME, Online System Marketing, Delivery Order, Tuwiri Tuban Abstrak.Determinasi teknologi sudah mengubah wajah dunia di segala sektor. Terutama sector industri dan perdagangan yang imbasnya sangat besar. Revolusi teknologi yang menyentuh segala sendi ekonomi dan sosial sangat memaksa semua pelaku bisnis untuk beralih dari yang konvensional-manual menuju teknologi digital. Kendati suatu keharusan, revolusi teknologi internet ini tidak serta merta bisa merangsek alih kendali. Masih dipertimbangkan bagaimana kondisi kesiapan masyarakat ekonomi Usaha Kecil dan Menengah dalam mengimplementasikan teknologi digital ini.Artikel ini merupakan serangkaian hasil riset dan pelayanan kepada masyarakat mengenai bagaimana menyiasati perubahan komunikasi pemasaran dari teknologi komunikasi analog-konvensional dan teknologi industri yang manual. Beberapa fokus yang akan dibahas antara lainmeliputi trik peningkatan daya saing UMKM Sentra Produksi Aneka Keripik melalui penerapanalih teknologi komunikasi pemasaran melalui transfer teknologi modern. Sasaran langsung ialah pada peningkatan produktifitas usaha hasil budidaya potensi daerah sektor perkebunan. Adapun basis obyek penelitian difokuskan pada sinergitas komunikasi antar lembaga yang berkaitan dengan pemasaran UMKM di desa Tuwiri kecamatan Merakurak Kabupaten Tuban Jawa Timurdan penerapan system komunikasi pemasaran yang dilakukan para pelaku bisnis UMKM ini termasuk penjajagan tatacara komunikasi pemasaran dan pola distribusi produk melalui sistem online dan delivery order.Kata kunci :Alih teknologi, Komunikasi Pemasaran, UKM, Online System Marketing, Delivery Order, Tuwiri Tuban